Challenges and Obstacles for Islamic Parties in Winning Elections - Didik Himmawan; Nazwa Anindita Maharani; Hylmy Malik Aziz (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to discuss the challenges and obstacles for Islamic parties in gaining votes in elections. Strategy in facing the Legislative Election is a challenge for contestants to make careful, precise and effective plans. This planning is prepared and implemented by the campaign team with the aim of achieving victory. Their target is to gain support from voters and increase electability. The research method used in this research is a qualitative method with a literature study approach, in the technique of reviewing and concluding various literature sources that are relevant to the research topic. The conclusion of this discussion is to examine Islamic politics from Al-Qur'an Surah Al Imran verse 159 concerning deliberation by examining the interpretation of Surah Ali Imran verse 159 from Tafsir Al-Maraghi, Tafsir Al-Misbah and Tafsir Al-Azhar, deliberation which is consensual is one of the values ​​and principles of Islamic politics in the Koran. These interpretations even suggest that the Prophet Muhammad SAW, as the leader of the Muslim community at that time, often took decisions suggested by his friends, not based on his own opinion. Islamic parties are closely related to understanding the relationship between Islam and politics. There are 2 (two) important reasons in examining Islamic parties in Indonesia, namely: First, even though the majority of the Indonesian people embraced Islam seriously or otherwise, the political position of Islam in that period was relatively weak. Second, the reason for studying this issue is because no special study has been carried out on the topic of Islam and its relevance to parties in practical political discourse so far. The importance of communication in political activities cannot be denied, and this also applies to political parties. Every political communication carried out always includes political messages, political communicators, media or political channels, and the effects that arise among the audience as a result of the political communication process. The formation of political parties is based on democratic principles, namely a government led by the majority through general elections.